Highly stereoselective synthesis of aryl/heteroaryl-C-nucleosides via the merger of photoredox and nickel catalysis. Issue 97 (20th November 2019) - Ma, Yingying; Liu, Shihui; Xi, Yifan; Li, Hongrui; Yang, Kai; Cheng, Zhihao; Wang, Wei; Zhang, Yongqiang
Abstract : A photoredox/nickel dual-catalyzed decarboxylative cross-coupling reaction of anomeric ribosyl/deoxyribosyl acids with aryl/heteroaryl bromides has been developed. Abstract : A photoredox/nickel dual-catalyzed decarboxylative cross-coupling reaction of anomeric ribosyl/deoxyribosyl acids with aryl/heteroaryl bromides has been developed. The reaction proceeds smoothly under visible-light irradiation and features the using of cost-effective and easily handled catalysts and starting materials, which allows the highly stereoselective synthesis of diverse aryl/heteroaryl- C -nucleosides in moderate to high yields.